Software Adoption, Employment Composition and the Skill Content of Occupations in Chilean Firms - Almeida, Rita K.; Fernandes, Ana M.; Viollaz, Mariana (Taylor and Francis, 2019)
We contribute to the technology, skills, and jobs debate by exploiting a novel data set for Chilean firms between 2007 and 2013, with information on the firms’ adoption of complex software used in client management, production, or administration and business software packages. Instrumental variables estimates show that, in the medium-run, adoption of this complex software reallocates employment away from professional and technical workers, toward administrative and unskilled workers (production and services). Adoption also increases the use of routine and manual tasks and reduces that of abstract tasks within firms. The contrast between ours and previous findings shows that labor market impacts of technology adoption hinge on the type of technology and its complementarity with the skills content of occupations.